A Polysilicon Learning Curve and the Material Requirements for Broad Electrification with Photovoltaics by 2050. Issue 10 (3rd August 2022) - Hallam, Brett; Kim, Moonyong; Underwood, Robert; Drury, Storm; Wang, Li; Dias, Pablo
Abstract : Herein, the current and future projected polysilicon demand for the photovoltaic (PV) industry toward broad electrification scenarios with 63.4 TW of PV installed by 2050 is studied. The current polysilicon demand by the PV industry in 2021 is equivalent to the consumption of 2.9–3.3 kt GW −1 . Depending on the physical constraints determining the lower limit for future polysilicon consumption, the annual demand can be 6–7 Mt year −1 in 2050 under broad electrification, which requires 10–12 times more of the current production capacity. To achieve broad electrification by 2050, cumulative demand of 46–87 Mt is required. An electricity requirement for purification, ingot pulling, and wafering of ≈360–380 kWh kg −1 for silicon wafers and carbon intensity can lead to a cumulative amount of ≈16.4–58.8 Gt of CO2‐eq emissions by 2050. To reduce the environmental impact, efficiencies are increased, thinner wafers are used, kerf loss reduced, alternative purification methods with low emission intensities are explored, and opportunities for polysilicon production with decarbonized electricity are explored. Abstract : Investigation of the current and future‐projected polysilicon demand, energy demand, and carbon footprint in the photovoltaics (PV) industry toward broad electrification scenarios with 63.4 TW of PV installed by 2050 is conducted.